2012
DOI: 10.1111/j.1365-2435.2012.02037.x
|View full text |Cite
|
Sign up to set email alerts
|

Kin recognition is density‐dependent and uncommon among temperate grassland plants

Abstract: Summary Some plant species may frequently encounter neighbourhoods composed of genetically closely related individuals. Such species should benefit from an ability to recognize kin and to display cooperative behaviour towards closely related neighbours. While kin recognition has been demonstrated in plants, previous studies have only examined single species in single environmental settings, making it impossible to draw conclusions about the prevalence of this behaviour in plants and its consequences in diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
58
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(63 citation statements)
references
References 59 publications
4
58
0
1
Order By: Relevance
“…In particular, the ability of plants to distinguish between members of the same or different accessions, the phenomenon of kin recognition (KR), has been well characterized. [8][9][10][11][12][13][14][15][16] Plants are generally thought to be incapable of processing complex visual or auditory cues, such as plumage or song, suggesting these sensory input channels are unavailable for KR. However cryptochrome-mediated KR has been observed in model organisms such as A. thaliana.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the ability of plants to distinguish between members of the same or different accessions, the phenomenon of kin recognition (KR), has been well characterized. [8][9][10][11][12][13][14][15][16] Plants are generally thought to be incapable of processing complex visual or auditory cues, such as plumage or song, suggesting these sensory input channels are unavailable for KR. However cryptochrome-mediated KR has been observed in model organisms such as A. thaliana.…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence that the outcome of belowground interactions between plants, of the kind illustrated in the previous set of examples, can be mediated by identity recognition, including species-specific responses (23)(24)(25)(26), kin/stranger responses (27)(28)(29)(30), and self/nonself responses (2, 3). Mahall and Callaway (23) found that root systems of the desert shrub Ambrosia dumosa appear to be capable of detecting and avoiding other Ambrosia root systems.…”
mentioning
confidence: 99%
“…Plant kin recognition and its contribution to plant coexi�te��e �atte��� a�e �till ���e��t��� i������ie�tl�, alt����� several works demonstrate their ecological relevance (File et al 2012, Lepik et al 2012, Karban et al 2013, Ehlers et al 2016. Nevertheless, further evidence is required to under-).…”
Section: Discussionmentioning
confidence: 99%
“…Given this, biomass alloca-). Given this, biomass allocation (Dudley and File 2007, Murphy and Dudley 200�, Bhatt et al 2011, Marler 2013, Semchenko et al 2014, Murphy et al 2017, reproductive traits (Milla et al 200�, Lepik et al 2012), spatial disposition of leaves (Crepy and Casal 2015), physiological mechanisms (Biedrzycki et al 2010, Biedrzycki andBais 2011a), molecular patterns (Biedrzycki a�� Bai� 2011b�, a� �ell a� i�t�a a�� i�te����e�i� � i�te�a�� �, a� �ell a� i�t�a a�� i�te����e�i�� i�te�a�-tions (Ehlers et al 2016) have been assessed with contrasting results (Lepik et al 2012, Semchenko et al 2017). However, with exception of work carried out by Karban et al (2013) regarding the role of volatile emission in plant kin recognition, most of these studies were achieved in pot with labopot with labowith laboratory or greenhouse settings, where conditions are far from t�at e�����te�e� ���e� �el� ����iti��� (Callaway and Mahall 2007).…”
Section: Introductionmentioning
confidence: 99%